Can design thinking succeed in your organization? - Dunne, David, 1953-; Eriksson, Theresa; Kietzmann, Jan (MIT Sloan Management Review, 2022)
Design thinking offers a way to make business decisions that is especially suited to exploring uncharted territory and solving complex problems. But leaders need to know when to apply it, and they have to prepare both their employees and managers to do so. The authors have identified the characteristics that make an organization “design thinking-ready” along with a strategic approach to adopting it.